2023
DOI: 10.1186/s13002-023-00605-4
|View full text |Cite
|
Sign up to set email alerts
|

The medicinal plant used in the Guangxi Fangcheng Golden Camellias national nature reserve, a coastal region in southern China

Abstract: Backgrounds Guangxi Fangcheng Golden Camellias national nature reserve, situated in Fangcheng City, Guangxi Province, China, is a coastal region renowned for its exceptional natural environment. Over time, the residents of this area have acquired extensive knowledge regarding medicinal plants, owing to their close association with the abundant flora. Our study aims to document the medicinal plants used by the local community near the Guangxi Fangcheng Golden Camellias national nature reserve. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The villagers who collected P. spicatum shared with us that consuming this plant can serve as a natural source of iron. Additionally, they mentioned that boiling the whole plant in water and using the resulting infusion externally may be effective in treating rheumatism, bruises, promoting blood circulation, and alleviating blood stasis [35]. The local residents near Shiwan Mountains are familiar with this plant and know precisely where it grows.…”
Section: Wild Vegetablesmentioning
confidence: 99%
“…The villagers who collected P. spicatum shared with us that consuming this plant can serve as a natural source of iron. Additionally, they mentioned that boiling the whole plant in water and using the resulting infusion externally may be effective in treating rheumatism, bruises, promoting blood circulation, and alleviating blood stasis [35]. The local residents near Shiwan Mountains are familiar with this plant and know precisely where it grows.…”
Section: Wild Vegetablesmentioning
confidence: 99%
“…Additionally, local people have found that boiling the whole plant in water and using the resulting infusion externally can be effective for treating rheumatism, bruises, promoting blood circulation, and alleviating blood stasis (Hu et al. 2023 ). Pentaphragma spicatum can be utilized as a source of domesticated species and can provide valuable genetic resources for the development of new crops through hybrid screening (Pandey et al.…”
Section: Introductionmentioning
confidence: 99%